Self-Healing and Mechanical Properties of Aged Hot Mix Asphalt Containing Waste Oil Capsules - Erdogan Yamac, Ozge; Yilmaz, Mehmet; Yalcin, Erkut; Ozdemir, Ahmet Munir; Garcia-Hernandez, Alvaro; Kok, Baha Vural (Springer Heidelberg, 2025)
Hot mix asphalts are known to have a self-healing property and microcracks in the pavement can close to some extent after they occur if they are not subjected to load and if sufficient time is allowed. However, this healing period is prolonged, and the healing rate is not very high. In this study, calcium alginate capsules containing waste vegetable oil and waste mineral oil as rejuvenating agents were produced, and used in asphalt mixtures at four different rates (0.25%, 0.50%, 0.75%, and 1.0%) by weight. The study aims to develop an environmentally friendly and economically viable repair method by using waste oils. Marshall stability and flow and tensile strength ratio tests were conducted on cylindrical specimens. Additionally, three-point bending test was performed on aged asphalt mixtures to determine the self-healing rates of cracks formed in the specimens. Fourier transform infrared spectroscopy was conducted on bitumen specimens taken before crack formation and after the healing period to determine the percentage of ruptured capsules in the mixture. The results showed that the addition of capsules containing waste mineral oil and vegetable oil reduced stability values and increased flow values. However, according to the results of the retained Marshall stability test, it was determined that the addition of capsules, especially at a 0.5% ratio, increased resistance to moisture damage. Regarding crack-healing results, it was found that temperature and curing time increased healing rates, and capsules containing waste mineral oil provided higher healing rates compared to those containing waste vegetable oil.
Keywords: Hot mix asphalt; Microcapsule; Waste oil; Three-point bending test; Self-healing